The Relation between Self-Regulation, Self-Efficacy and Achievement Motivation among Muslim Students in Senior High Schools - Sabrina, Rifdah; Risnawati, Risnawati; Anwar, Khairil; Hulawa, Djeprin E.; Sabti, Fajri; Rijan, Mohd Hakim Bin Mothar; Kakoh, Nur Asikin (International Journal of Islamic Studies Higher Education, 2023)
This research was conducted to analyze the relationship between self-regulation and self-efficacy in the context of achievement motivation among Muslim Senior High School students in Indonesia. A quantitative correlational method was used, and data sources were collected through a questionnaire with a four to five-point Likert scale. A total of 565 respondents, drawn from a population pool of 1,568, were selected using a simple random sampling technique. Furthermore, data were analyzed through bivariate and multivariate correlation techniques using SPSS Version 20 software. The results showed that, first, there was a significant positive correlation between self-regulation and achievement motivation of students. Second, a positive correlation of statistical significance was evident between self-efficacy and achievement motivation. Third, a strong and significant positive correlation was reported when simultaneously considering self-regulation and self-efficacy. This research served as evidence of self-regulation and self-efficacy in shaping academic performance of students during the academic pursuits. Therefore, the two variables should be accorded significant attention and concern by stakeholders, with a particular emphasis on teachers and parents.